1997
DOI: 10.1095/biolreprod57.2.335
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Onset of Menopause in the Rhesus Macaque1

Abstract: The objective of this study was to assess ovarian activity in a cohort of aged female rhesus macaques. Menstrual records for 26 rhesus macaques ages 20-29 yr were evaluated over a 1-yr period, and daily urinary estrone conjugate (E1C) and pregnanediol-3-glucuronide (Hygeia [Hy]-PdG) levels were determined for 12 wk. Each animal was categorized as either pre-, peri-, or postmenopausal based on menstrual and hormonal data. Eleven animals (mean age 22.5 yr) were premenopausal, thirteen (mean age 24 yr) were perim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
135
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(144 citation statements)
references
References 13 publications
9
135
0
Order By: Relevance
“…Evidence reported to date supports the idea that macaques go through physical changes associated with reproductive senescence, reminiscent of changes observed during human menopause. Studies involving ovarian, hormonal, and pituitary function of aging rhesus macaques (Hodgen et al 1977, Gilardi et al 1997, Gore et al 2004, Nichols et al 2005, Schramm et al 2002 have consistently shown biological changes mirroring those known to occur in women and support the macaque as an adequate model of human menopause. In Japanese macaques, a decrease in ovarian control of gonadotropin levels has been reported in monkeys approximately at age 18 (Nozaki et al 1995).…”
Section: Ttd (Years)mentioning
confidence: 85%
See 2 more Smart Citations
“…Evidence reported to date supports the idea that macaques go through physical changes associated with reproductive senescence, reminiscent of changes observed during human menopause. Studies involving ovarian, hormonal, and pituitary function of aging rhesus macaques (Hodgen et al 1977, Gilardi et al 1997, Gore et al 2004, Nichols et al 2005, Schramm et al 2002 have consistently shown biological changes mirroring those known to occur in women and support the macaque as an adequate model of human menopause. In Japanese macaques, a decrease in ovarian control of gonadotropin levels has been reported in monkeys approximately at age 18 (Nozaki et al 1995).…”
Section: Ttd (Years)mentioning
confidence: 85%
“…An increase in gonadotropin releasing hormone concentrations, associated with a reduction of estrogen at menopause, has also been reported in aged rhesus monkeys (Gore et al 2004). Aging rhesus monkeys experience irregular menstrual cycles and long follicular phases due to delayed ovulation (Gilardi et al 1997). Moreover, Schramm et al (2002) found that as monkeys age, serum follicle stimulating hormone (FSH) levels increase, peak estradiol levels during hyperstimulation decrease and oocyte retrieval numbers are lower when compared with younger animals, which is consistent with what is commonly seen in older women.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Despite the absence of seasonality in terms of food availability, individuals were still exposed to seasonal changes in day length and temperature, both important factors driving seasonal breeding and reproductive hormone secretion (Wingfield 1984). A negative correlation between fertility and age has been observed for a number of primate species including hanuman langurs (Presbytis entellus, Borries et al 1991), rhesus macaques (Macaca mulatta, Gilardi et al 1997;Shideler et al 2001) and olive baboons (Papio anubis, Strum and Western 1982). Although the average age of our captive female group was 3.6 ± 1.3 years (range: 2-5), thus at the chronological age of peak reproductive potential, the biological age of the ovaries could be at an advanced stage, influencing ovarian endocrine activity.…”
Section: Discussionmentioning
confidence: 99%
“…Reproductive physiology and aging in Rhesus monkeys closely model these processes in women [42]. Rhesus monkeys live about 35 years, reach puberty at 3-5 years old, ovulate one egg each month, and maintain fertility for about 20 years, after which follicle numbers decline, and menopause ensues [43,44]. We tested the hypothesis that DNA damage increases and the DNA repair protein BRCA1 decreases in granulosa cells with advancing age in the Rhesus monkey.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%